Space data processing pipeline for PASO - Gonçalves, Luís Filipe Pino (2023)
Orbital debris have become one of the biggest threats for operational satellites. With an increase in satellite launches the number of small objects in orbit is increasing at a never seen rate. This has created the need to track and survey these objects in order to protect present and future space missions. As part of the SST, Portugal is creating PASO (PAmpilhosa da Serra Observatory) with the main mission of monitoring objects in all orbits. It is already equipped with a radar telescope capable of tracking LEO objects and a optical telescope capable of surveying and tracking MEO and GEO objects. In this thesis we developed SPADE, the new space data pipeline that will be used for the new double telescope system being now implemented in PASO. This pipeline consists of all the steps necessary to analyse a raw image: image reduction, source detection, plate solving with additional possibility of photometry and satellite identification. SPADE is presently ready to analyse MEO and GEO orbits reaching the necessary 2 arcsec precision required by the SST and will continue to be worked on with the final goal of analysing LEO objects. SPADE was built with the goal of providing real-time analysis without the creation of image queues. This was achieved by the usage of multi-threading. SPADE was also built to be easily adaptable to any telescope and observatory. Every part of the pipeline can be easily controlled in the configuration file without the need of in-depth knowledge of the code.